A Faculty Workshop on Developing Students as Discipline-Situated Researchers - William Badke; Elizabeth Kreiter; Qinqin Zhang (Communications in Information Literacy)
The reference librarians of Trinity Western University have a strong mission-driven commitment to teach information literacy, but there is a significant contrast between the amount of instruction they can provide and the demanding task of developing all students as skilled researchers. The growing teach-the-teacher model suggested an option to enlist faculty in providing a larger portion of information literacy instruction themselves. With strong support from academic administration, three librarians devised an initial faculty workshop as part of the university’s faculty professional development series, followed by four detailed weekly sessions. They based their activities on several factors: first, faculty members would need to be invited into a shared concern about student research; second, the librarians would not call for significant disruption of current curricula and teaching practices; and third, the workshops would focus on one basic idea—turning the assigned research project into a vehicle for developing students as researchers—rather than overwhelming faculty with multiple options. Faculty responded positively to the workshop series, and there are initial signs that faculty members are embracing the promoted concepts.